What editorial standards should be adopted by newspapers in relation to letters that contain health claims? - Peto, TJ; Pukrittayakamee, S; Callery, JJ; Phumratanaprapin, W (Royal Society of Thailand, 2020)
Newspapers have a responsibility to report the truth to their readers, and the trustworthiness of the print media remains crucial in our age of decentralized, social media and online commentary. Honest reporting of the evidence and the uncertainties around health claims are especially important as there may be serious consequences if incorrect information is disseminated. Letters to the Editor can fall into a grey area where the responsibility for statements are unclear. Recently there have been examples of misleading claims printed in letters appearing in many local and English language newspapers in many countries. One letter to a newspaper in Thailand made incorrect statements about vaccine safety which, if believed, could potentially discourage infant vaccination and thereby place children at risk of preventable infectious diseases. Another letter contradicted Thailand’s national policy for malaria treatment with artemisinin combination therapies and advocated instead the use of unlicensed, unproven herbal remedies, which if followed could result in the mismanagement of a potentially fatal disease. Both articles risked causing harm and should not have been printed without qualification.